Abai’s Concept of the “Moral Personality” through the Lens of Trauma Studies - Demessinova Л.М.; Aubakir Ж.М. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2025)
This article examines the after-effects of historical and social trauma preserved in the collective memory and unconscious of the Kazakh people through Abai Kunanbaev’s concept of the “moral personality.” Drawing on trauma theory, the authors analyse the spiritual crisis, moral degradation and erosion of the national code that emerged under colonial oppression and trace their manifestations in contemporary Kazakhstani society. The theoretical frameworks of Z. Freud, J. Alexander, R. Eyerman and C. Caruth are employed to interpret Abai’s literary images and motifs in the context of collective and historical trauma. Abai’s notion of the “moral personality” is presented as a key mechanism for spiritual healing and the preservation of national identity. A comparative analysis of the spiritual-moral condition of Kazakh society in Abai’s era and today reveals the long-term consequences of collective trauma, its recurrence and its intergenerational transmission. The synthesis of modern research methods allows Abai’s oeuvre to be re-evaluated as a spiritual resource capable of treating the nation’s collective trauma.